Internal audit effectiveness as a boon to public procurement performance: a multi mediation model - Michael Karikari Appiah; Newman Amaning; Paul Kwaku Tettevi; Daniel Frimpong Owusu; Emmanuel Opoku Ware (Cogent Economics & Finance, 2023)
As part of Governments of Ghana efforts to deal with misappropriation of public sector resources, the Internal Audit Agency Act, 2003 (Act 658) was established to ensure probity, accountability, and transparency in the management of public sector resources, yet there is a high Corruption Perception Index in Ghana as asserted by the Transparent International 2021 release. To address this concern, our paper is aimed to develop a new model to explain the extent to which internal audit effectiveness (IAE) could be used to build strong organizational resilience as a mechanism through which efficiency in public procurement could be achieved while reducing public sector corruption incidence. Data have been collected from a cross-section of public sector workers. The structural equation modeling approach has been used to analyze the survey data. Our results have shown that cultural, and strategic resilience dimensions of organizational resilience significantly mediate the relationship between IAE and procurement performance. These results have implications for re-enforcement of audit regulations to ensure transparency in managing public sector resources with a focus on reducing negative public sector corruption perception.
Keywords: 330; Ghana; Internal audit effectiveness; organizational resilience; procurement performance; SEM